2002
DOI: 10.3406/tiers.2002.1596
|View full text |Cite
|
Sign up to set email alerts
|

Travail domestique et travail des enfants, le cas d'Abidjan (Côte-d'Ivoire)

Abstract: [eng] Mélanie Jacquemin — Domestic work and child labour : the case of Abidjan (Ivory Coast.). Invisible for a long while or rendered as such, child labour is now in the spotlights due to the present focus on the extreme aspects of child-exploitation. In Ivory Coast, the phenomenon of little servants is undergoing significant changes, combining traditional educational practices through work with more recent wage concerns. Observing the diversity of situations suggests that indiscriminate abolition would be dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 4 publications
0
5
0
4
Order By: Relevance
“…This applies to street children, belonging to the category used by UNICEF 'children in especially difficult circumstances' (Black 1996), who are excluded in the DHS sample, because this survey is drawn on households' base. In the same category, despite recent efforts to estimate their prevalence 6 , working children remain underdeclared in surveys, in particular domestic children who are well known as prevalent in Africa (Delaunay and Enel 2009;Destremau and Lautier 2002;Jacquemin 2002). Second, if some children are in any situation of abandonment outside family, a large part of the others live with their kin and familial solidarity allows them (more or less) to confront crisis situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This applies to street children, belonging to the category used by UNICEF 'children in especially difficult circumstances' (Black 1996), who are excluded in the DHS sample, because this survey is drawn on households' base. In the same category, despite recent efforts to estimate their prevalence 6 , working children remain underdeclared in surveys, in particular domestic children who are well known as prevalent in Africa (Delaunay and Enel 2009;Destremau and Lautier 2002;Jacquemin 2002). Second, if some children are in any situation of abandonment outside family, a large part of the others live with their kin and familial solidarity allows them (more or less) to confront crisis situations.…”
Section: Discussionmentioning
confidence: 99%
“…Child transfers are also sometimes motivated by economic reasons. For several decades, schooling access is a cause for entrusting a child to the care of an urban family in exchange of some domestic work (Jacquemin 2002;Jonckers 1997;Vandermeersch 2002). …”
Section: New Forms Of Circulationmentioning
confidence: 99%
“…Como atestiguan las investigaciones realizadas en el Perú (Young, 1987), en Brasil (Lautier, 2002), en Canadá (Bakan, Stasiulis, 1997) o en Costa de Marfil (Jacquemin, 2002), este discurso aparece como un hecho transnacional, quizás en la misma medida que la asignación del trabajo de reproducción no remunerado a mujeres y a niñas. El rol mayor del familismo en lo que concierne el trabajo doméstico remunerado, ha hecho correr ríos de tinta, pero la mayor parte de estos estudios se han centrado en el familismo en el interior de los hogares de los empleadores.…”
Section: Falsa Concienciaunclassified
“…Recent work has shown that such practices can also lead to the exploitation of children as cheap labour in the sphere of the home. See, for example, Jacquemin (2002Jacquemin ( , 2006.…”
Section: Notesmentioning
confidence: 99%